Petro Geoscience 1. IN SITU STRESSES IN SEDIMENTARY ROCKS (PART 1): MEASUREMENT TECHNIQUES - Bell, J. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1996)
Summary This paper is the first of two that review recent research involving in situ stresses in sedimentary rocks and the geological and petroleum engineering applications of these data. Part I describes and discusses the most commonly used methods for measuring today's rock stresses in sedimentary rocks, in terms of Sv {vertical principal stress), SHmax (larger horizontal principal stress) and SHmin (smaller horizontal principal stress). Stress magnitudes may be obtained from density logs (Sv), from hydraulic fracture tests and leak-off tests (SHmm) as well as from core monitoring techniques (SHmin, SHmax). Borehole slotting holds promise for use in deep wells (SHmln, SHmax), but is not yet operational. Near-surface stress orientations (SHmirv SHmax) can be inferred from a variety of geological indicators, provided precautions are taken in selecting locations. Subsurface stress orientation data are provided by breakouts (SHmm. SHmax) specific types of core fractures (SHmin, SHmax) and core discing (SHmax), as well as by core expansion (SHmin. SHmax), hydraulic fractures (SHmax), drilling-induced fractures (SHmax), and earthquakes (SHmax). Acoustic an isotropy and shear wave splitting will indicate microfracture orientation, which may or may not coincide with contemporary stress axes. All these methods are in common use today, especially within the oil industry.